In vitro bioactivity of biodegradable films based on chitosan/quince seed mucilage reinforced with ZnO-nanoparticle - Emir Coban, Ozlem; Akat, Zelal; Karatepe, Pinar; Incili, Goekhan Kuersad (Springer, 2024)
In this study, biodegradable active films were designed by adding ZnO-NPs to the quince seed mucilage/chitosan matrix. The films were investigated for characterization and in vitro bioactivity. According to the results, a significant decrease in moisture content, water holding capacity and light (L*) occurred with the addition of ZnO-NP. (p < 0.05). FT-IR spectra showed the interaction between ZnO-NPs and N-H quince seed mucilage and chitosan groups. Nanocomposite films containing ZnO-NP showed improved thermal stability. The developed bionanocomposite films were easily buried in soil and subjected to degradation. The minimum degradation of the film in soil after 20 days was 62.02%. The maximum cell viability (%) of C/ZnO-NP and C/QSM/ZnO-NP films were determined as 86.81% and 91.22%, respectively, and the films were found to be non-toxic. Moreover, while the quince seed mucilage film did not show antibacterial performance, chitosan and ZnO NPs showed antibacterial effects against the tested bacteria Listeria monocytogenes (ATCC 7644) and Escherichia coli O157:H7 (ATCC 35,150). In this context, the design bionanocomposite films can be used as an active food packaging material for food preservation by controlling food-borne pathogens. In addition, the developed films do not pose a threat to the environment and therefore have great potential for the sustainable food packaging industry.
Keywords: Biodegradable film; Antimicrobial activity; Quince seed mucilage; Nanoparticle; Soil degradation